HUBUNGAN STRUKTUR ORGANISASI DENGAN EFEKTIFITAS KERJA PEGAWAI NEGERI SIPIL - Zain Noktah Asli (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
This study aims about relationship of organization structure with job effectivity. The method is explanatory survey research so date was got based on sample form all of population. Number of sample are 34 people which was got random on simple random. To know exist or not relationship used statistic test of Spearman Rank Correlation Coefficient.Based on analysis result can be explain, that the effectivity grade of officer work on education and culture service look good. Accourding to three indicator which was measured is job productivity, job efficiency, and job satisfication and follow in all of responden opinion look good. This means job effectivity of officer which was not optimal is causal from organization structure was not applicated exactly yet.From aspect for organization structure less support to job effectivity lock by share job which less with need of officer and the deparity treatment make the officer apt to character not constructive. Although in share of job as rule accourding to normative rule and as to organization structure but implementative only take the name of organization personnel, and the irony is not all of officer understand what the job description.